Copping a 'copter. (Economist, 2015)
The article focuses on research into methods of detecting and grounding rogue drone aircraft. It comments on incidents of rogue drones including a drone crash on the U.S. White House lawn and drones flying past French nuclear plants. It mentions startup DroneShield is developing a system to detect drones based on the sounds they make while Blighter Surveillance Systems uses radar and the Doppler effect. It talks about methods of stopping drones including computer hacking and anti-drone drones.